A Review of Property Enhancement Techniques for Carrageenan-based Films and Coatings. (15th July 2019) - Sedayu, Bakti B.; Cran, Marlene J.; Bigger, Stephen W.
Highlights: Carrageenans are a source of renewable, sustainable polymers derived from seaweeds. Limitations of carrageenan films arise from their inherent hydrophilicity. Blending, reinforcement, and multi-layering can enhance film properties and extend potential applications. Blends with nanocellulose can improve tensile strength by 50%. Films layered with poly(lactic acid) can reduce water vapor permeability by 24-fold. Abstract: Carrageenan, a polysaccharide extracted from marine algae, is becoming increasingly regarded as a promising renewable biomaterial that has strong potential as a substitute for conventional synthetic plastics. Materials derived from carrageenans have been widely investigated over the recent decades for use in pharmaceutical and biomedical applications through to edible films and coatings. In the area of flexible films, carrageenans suffer from limitations that are primarily a result of their inherent hydrophilicity. Considerable research efforts have been devoted to the improvement of the properties of carrageenan films in order to extend the range of suitable applications. These include blending with other polymers, the use of plasticizers, and reinforcements with nanomaterials. This review comprehensively assesses the current status of carrageenan-based film development including material characteristics and strategies to obtain desirable film properties with particular regard to real applications.